The efficacy of targeted therapy combined with radiotherapy and temozolomide-based chemotherapy in the treatment of glioma: A systemic review and meta-analysis of phase II/III randomized controlled trials - Ma, Yifan; Wang, Yue; Nie, Chen; Lin, Yongzhong (Frontiers in Oncology, 2023)
Background Glioma is the most common intracranial tumor, accounting for about half of the primary intracranial tumors, with the characteristics of hidden onset and high mortality. Even after surgery, radiotherapy and chemotherapy, the prognosis of glioma is not ideal. Targeted therapy has developed rapidly in the treatment of other malignant tumors, which is also an important direction in the research and development of new therapies for glioma. So far, targeting combined with radiotherapy and chemotherapy have been used as the treatment of glioma in many clinical trials, but the role of targeted combined radiotherapy and chemotherapy in the treatment of glioma is still controversial. The purpose of this study was to evaluate the efficacy of targeted therapy combined with radiotherapy and temozolomide (TMZ)-based chemotherapy in the treatment of glioma. Methods Phase II or phase III clinical trials involving targeted therapy combined with radiotherapy and chemotherapy and temozolomide-based radiotherapy and chemotherapy for gliomas were searched using PubMed, Embase and Web of Science databases, and a comprehensive meta-analysis was conducted. The primary outcome was overall survival time (OS) and progression-free survival time (PFS), and the secondary outcome was adverse reaction. The time-to-event data is summarized as hazard ratio (HR), and the binary results are summarized as odds ratio (OR). Two researchers conducted literature screening, data extraction and quality evaluation according to inclusion and exclusion criteria. Stata16.0 software was used for analysis, random effect model was used for data merging, and forest map was used for display. Results A total of 11 eligible literatures and 12 prospective randomized controlled clinical trials of 1284 cases were included in the meta-analysis. The results showed that compared with radiotherapy and chemotherapy alone, targeted drugs combined with temozolomide-based radiotherapy and chemotherapy could significantly improve OS in phase II trial, but there was no improvement in Phase III trial, and PFS of newly diagnosed glioma patients was improved (HR=0.82(0.71-0.94) 95%CI, p =0.005). The PFS of the third phase of the experiment also improved. Compared with radiotherapy and chemotherapy alone, there was no statistically significant increase in adverse events in targeted combined radiotherapy and chemotherapy group. Systematic review registration https://www.crd.york.ac.uk/prospero, identifier CRD42022326012.